Emotional Intelligence Correlates with Reduced Quarter Life Crisis Among Female Students: Kecerdasan Emosional Berkorelasi dengan Berkurangnya Krisis Seperempat Kehidupan di Kalangan Mahasiswi - Nadya Alisarani; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Early adulthood is a developmental phase marked by identity exploration, life transitions, and psychological challenges. Specific Background: University students in the emerging adulthood stage frequently encounter academic, career, financial, and interpersonal pressures that may lead to quarter life crisis, while emotional intelligence is associated with emotional regulation and coping abilities. Knowledge Gap: Empirical studies examining the relationship between emotional intelligence and quarter life crisis specifically among female university students remain limited. Aims: This study aims to examine the relationship between emotional intelligence and quarter life crisis among female students at Muhammadiyah Sidoarjo University. Results: Using a quantitative correlational design with quota sampling of 200 female students, data were collected through Likert-scale instruments consisting of an emotional intelligence scale (33 items; reliability = 0.729) and a quarter life crisis scale (20 items; reliability = 0.830). Pearson product moment correlation analysis using JASP 16.0 revealed a significant negative relationship between emotional intelligence and quarter life crisis (rho = -0.68, p < .001). Novelty: This study provides empirical evidence emphasizing emotional intelligence as a psychological correlate of quarter life crisis among female university students. Implications: The findings indicate the importance of developing emotional recognition, regulation, and expression strategies to address quarter life crisis during emerging adulthood. Highlights: Higher Emotional Regulation Capacity Corresponded With Lower Psychological Instability During Early Adulthood Transition. Significant Statistical Association Was Identified Between Emotional Competence and Transitional Life Stress Conditions. Emotional Awareness and Expression Strategies Were Linked to Reduced Crisis-Related Experiences Among Participants. Keywords: Emotional Intelligence, Quarter Life Crisis, Female University Students, Emerging Adulthood; Pearson Correlation